Programa de estrategias didácticas para el desarrollo de la inteligencia espiritual en directivos y docentes de la Institución Educativa Pública Nivel Inicial N° 158 Mi Segunda Casita San Juan Bautista 2022 - Bartra Quiñones, Rosa Angélica (2024)
The research is based on the fundamental question: What is the effect of the application of the program of didactic strategies for the development of spiritual intelligence in managers and teachers of the public educational institution initial level N ° 158 My Second House San Juan Bautista 2022?, and as an objective to evaluate the effect of the application of the program of didactic strategies for the development of spiritual intelligence in managers and teachers. Its design is field, evolutionary, univariate, transectional and evaluative type, pre-experimental, single group. 22 managers and teachers made up the population and sample. Through the survey technique, data were collected using an instrument validated in advance by experts. The effect of the didactic strategies on the development of the spiritual intelligence of the managers of the public institution initial of San Juan district after the hypothesis test, the results indicate that there was a statistically significant difference between the levels before and after the experiment (p<0.05). The deficient level was reduced from 40.9% (n = 9) to 0%, the process level increased from 59.1% (n = 13) to 63.6% (n = 14), the sufficient level increased from 0% (n = 0) to 22.7% (n = 5) and the outstanding level increased from 0% (n = 0) to 13.7% (n = 3). These results show a substantial improvement in the spiritual intelligence of managers and teachers because of applying didactic strategies.